Analysis of Babi Reservoir Water Management for Irigation and Raw Water in Puyung Village Jonggat District Central Lombok Regency - Nurul Hijah, Siti; Kendimansyah, Muhammad (Universitas Ibn Khaldun Bogor, 2023)
Babi Reservoir is located at Puyung Village Jonggat District Central Lombok Regency, which accomodate water from HLD (High Level Diversion) Channel of Jurang Sate located in DAS Dodokan is being used to fulfil the irrigation requirement during dry seasons and utilized for various requirement in agriculture fields, livestock and communities. The area of DTA (Catchment Area) of Babi Reservoir are 6,43 km2, potential areal at the location of Babi Reservoir are 150 ha ((Balai Wilayah Nusa Tenggara I, 2021)). Embung Babi services has been not fully utilized by surrounding communities. The availability of water is insufficient, thus the optimization of Embung Babi is essential so the reserved water can be optimally used. This research used evaluative method, by doing collection of primary and secondary data. For maximizing the area of irrigation land, optimization of the irrigation area is carried out by applying cropping pattern, namely Paddy-Paddy-Palawija with type of Palawija is soybean. In optimization model that used is monthly optimization within 1 year by calculation the area of irrigation land that available, area of fulfilled irrigation area, the amount of water availability, and the fulfilled requirement of water for irrigation. Optimization method that being used in this calculation is Program Solver. Based on the result of optimization of Babi Reservoir water potential that available for maximum area of irrigation land with cropping pattern Paddy-Paddy-Palawija in early planting of November II with land area of 138,52 ha and planting intentisity of 92,35% within one year. During MT I the irrigation area are 18,83 ha and planting intensity of 12,55%. During MT II the irrigation area are 89,98 ha and planting intensity of 59,99%. Amd for MT III the irrigation area are 29,71 ha and planting intensity are 19,81%.